Contribution to the taxonomy and distribution of Bupleurum boissieri, B. aequiradiatum and B. gerardi (Apiaceae) in the Balkans - Stoyanov, Stoyan (Phytotaxa, 2019)
Bupleurum uechtritzianum, recently described from Bulgaria, is synonymized with B. boissieri. Bupleurum boissieri, so far known for Georgia, Syria, and Turkey (Asia Minor), first becomes recognized for the Balkans (Northeastern Bulgaria and Romanian Dobrogea) and the Crimea. Bupleurum aequiradiatum, endemic to the Balkans, is reported from Romania for the first time, and is excluded from Albania and Croatia. Bupleurum gerardi does not occur in the Balkans and its records in Bulgaria belong to B. commutatum. The lectotype of B. aequiradiatum is also designated here. A dichotomous key to the Balkan representatives of Bupleurum section Juncea and close-up photographs of their diagnostic characters are provided.